1996
DOI: 10.1038/bjc.1996.55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transient expression of the oestrogen receptor on constitutive and inducible CYP1A1 in Hs578T human breast cancer cells

Abstract: Summary Hs578T human breast cancer cells are an oestrogen receptor (ER)-negative cell line. Treatment of these cells with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) resulted in formation of a 6.9 S nuclear aryl hydrocarbon (Ah) receptor complex, which bound to a [32P]dioxin-responsive element in a gel electrophoretic mobility shift assay. However, TCDD does not induce CYPlAl gene expression or chloramphenicol acetyl transferase (CAT) activity in cells transiently transfected with pRNHllc or pMCAT5.12, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
1
11
1
Order By: Relevance
“…(Previous reports indicated some difficulty in inducing CYP1A1 promoter-driven CAT reporter activity in human tumor cells ( (Thomsen et al, 1994;Wang et al, 1996). However, we have noted that the ease with which AhR-dependent reporter activity is induced is highly sensitive to culture conditions, with confluent or near-confluent monolayers downregulating their AhR levels and CYP1A1 inducibility.)…”
Section: Discussionmentioning
confidence: 82%
“…(Previous reports indicated some difficulty in inducing CYP1A1 promoter-driven CAT reporter activity in human tumor cells ( (Thomsen et al, 1994;Wang et al, 1996). However, we have noted that the ease with which AhR-dependent reporter activity is induced is highly sensitive to culture conditions, with confluent or near-confluent monolayers downregulating their AhR levels and CYP1A1 inducibility.)…”
Section: Discussionmentioning
confidence: 82%
“…It has also been previously demonstrated that CYP1A1 induction is influenced by the estrogen receptor (ER) and that a functional ER is required for this activation (13)(14)(15). In more recent studies, it was demonstrated that the presence of 17-ß estradiol (E2) in ovariectomized rats could significantly influence the induction of CYP1A1 by TCDD (16).…”
Section: Introductionmentioning
confidence: 99%
“…How- tent, 24) and Ah responsiveness is dependent not only on the expression of AhR but also ER-α levels. [24][25][26] ER-negative breast cancer cell lines such as MDA-MB-231 and Hs578T are normally not responsive to Ah, but transient transfection of ER-α into these cells restores their Ah responsiveness. 25,26) Detailed sequential reporter gene assays have revealed that both the N-and C-terminal transactivation domains of ER-α are responsible for AhR responsiveness.…”
Section: Influence Of Estrogen On Tcdd-induced Xre Transactivation Inmentioning
confidence: 99%
“…[24][25][26] ER-negative breast cancer cell lines such as MDA-MB-231 and Hs578T are normally not responsive to Ah, but transient transfection of ER-α into these cells restores their Ah responsiveness. 25,26) Detailed sequential reporter gene assays have revealed that both the N-and C-terminal transactivation domains of ER-α are responsible for AhR responsiveness. 26) The mechanisms involved are unclear, but several possibilities can be speculated: 1) ER-α might interact with liganded AhR-ARNT complexes directly or through some bridging factors; and 2) ER-α might displace negative regulatory factors or facilitate the binding of critical transcription factors to the upstream promoter region.…”
Section: Influence Of Estrogen On Tcdd-induced Xre Transactivation Inmentioning
confidence: 99%
See 1 more Smart Citation